Distribution characteristics and origin analysis of iron and manganese in groundwater in Beijing Plain Area - Jiji CHEN; Lei TAO; Baoxian LIU; Qing YANG; Yue XI; Sushi XU; Yuanyuan CHEN; Hongwei JING (Shuiwen dizhi gongcheng dizhi)
Groundwater is an important part of Beijing’s water supply, excessive ferric and manganese in groundwater will limit the development and utilization of water resources. The spatial distribution, geochemical characteristics, and sources of ferric and manganese in groundwater were analyzed based on X-ray fluorescence spectrometry, iron and manganese step extraction method, geological statistical analysis, and GIS spatial feature analysis. Results show that the iron concentration in groundwater in the study area ranged from 0.02 to 26.7 mg/L, with an average of 0.76 mg/L, and the manganese concentration ranged from 0.01 to 5.24 mg/L, with an average of 0.21 mg/L. The distributions of iron and manganese in groundwater were basically consistent, showing a trend of gradually increasing along the groundwater flow direction (from northwest to southeast) and gradually decreasing with the increase of sampling depth. The mass ratio of iron in the deposits ranged from 9.25 to 52.18 g/kg, with an average of 19.90 g/kg, while the mass ratio of manganese ranged from 0.12 to 7.26 g/kg, with an average of 0.50 g/kg. The mass ratios of iron and manganese in the sediments in the whole city did not show a distribution pattern similar to that in groundwater. However, there were positive correlations between the proportion of active component iron and the iron in groundwater (R=0.66, P>0.05), and between the content of active component manganese and the manganese concentration in groundwater (R=0.84, P<0.05). It can be considered that the enrichments of iron and manganese in groundwater in the study area are related to the active components of iron and manganese in sediments. They are affected by hydrogeological conditions such as slow groundwater runoff rate, high clay specific gravity, reduction environment, and pH. Human activities are not the main factors that cause excessive iron and manganese in groundwater. This study provides valuable guidance for the local government in improving the management and utilization of groundwater resources.